Pelatihan Public Speaking Bagi Mahasiswa Untuk Seminar Proposal dan Hasil Sidang Skripsi - Suharti Sirajuddin; Faradilla Mesfer (Yayasan Habiburrahman Jamalu Bina Ummat, 2023)
The purpose of this community service activity was to train students’ public speaking skills to perform presentation at seminar proposal and research result seminar. This training was based on the low performance of students’ public speaking when performed in seminar presentation for both proposal or result seminars. The implementation for this training program focused on practiced rather than theory of public speaking. The reference for this training started with the introduction and filling out the survey regarding their goals and expectations for participating in this training, then proceed with the presentation of tips and tricks to become a presenter by practicing public speaking method which was called ‘1 minute challenge’. After that, there was evaluation from that practice, and lastly at the end of the training the participants presented full seminar presentation for proposal or result seminar. The result of this study showed the enthusiasm of the training participants, who from the beginning to the end showed their active participations. The method was used in this training which focused on practiced rather than theory proved that effective